Implementasi Algoritma Dijkstra Untuk Analisis Rute Transportasi Umum Transjogja Berbasis Android - Sunardi, Sunardi; Yudhana, Anton; Kadim, Ahmad Azhar (JSINBIS (Jurnal Sistem Informasi Bisnis), 2019)
TransJogja is one of the public transportation media used by Yogyakarta residents. Currently TransJogja has served many passengers with various routes and has become a favorite transportation for locals and tourists visiting Yogyakarta. TransJogja continues to provide the best services for its users to attract potential passengers. Lack of information about bus routes and stops creates a negative impression for TransJogja users such as using the bus or going down to the bus which is not the destination of the user. This study aims to implement and analyze the TransJogja route using the Dijkstra Algorithm and utilize Android as its medium so that it can increase the interest of Transjogja users and facilitate service. Dijkstra Algebra is an algorithm to find the best route by comparing all the good weights in terms of distance, time and route to be passed. The weight used is the distance between stops. In this study obtained the best route results with a shorter execution time of <0.0076 seconds and the results of the route obtained can be displayed to an Android-based mobile device as expected. Using the developed application is expected to be a solution to be applied to TransJogja and other public transportation.